The enforcement of discipline in the Royal Malaysian Police Force: An administrative law perspective / Arifai Tarawe - Arifai, Tarawe (2010)
The Royal Malaysian Police Force is a huge organization which consists of more than hundred thousand personnel from a different background of socio-demography. Although there are many courses and training being organized to uphold integrity and discipline among police officers, disciplinary problems still arise.